TAFRO syndrome: A case report and review of the literature - Tieying Hou; Jaspreet Dhillon; Wenbin Xiao; Elaine S. Jaffe; Amy M. Sands; Vishala Neppalli; George Deeb; Nan Zhang (Elsevier, 2017)
TAFRO syndrome is a rare clinicopathologic variant of idiopathic multicentric Castleman disease characterized by Thrombocytopenia, Ascites (anasarca), myeloFibrosis, Renal dysfunction, and Organomegaly. Here, we report a case of TAFRO syndrome in an HIV-negative young Caucasian male who presented with fever, normocytic anemia, thrombocytopenia, and acute renal insufficiency. The serum interleukin-6 (IL-6) level was elevated. Chest and abdominal CT revealed bilateral pleural effusion, ascites, splenomegaly, and multiple mildly enlarged lymph nodes. An excisional biopsy of inguinal lymph node showed a few atrophic follicles and expansion of interfollicular areas by marked vascular proliferation and polytypic plasmacytosis. HHV-8 was negative. Subsequent bone marrow biopsy was normocellular with moderately increased megakaryocytes and occasional megakaryocytic emperipolesis. His signs and symptoms improved after treatment with methylprednisolone and tocilizumab (anti-IL-6 receptor antibody). Our study confirms the distinctive nature of this syndrome, which should allow for better recognition and appropriate therapy. Keywords: Castleman-Kojima disease, TAFRO syndrome, Idiopathic multicentric Castleman disease, IL-6, HHV-8